PERMUKIMAN DAERAH PEDALAMAN DAN DAERAH PANTAI SITUS TEMPURSARI - Goenadi Nitihaminoto (BRIN, 1996)
Settlements in the coastal area follow a longitudinal pattern along the coast which can still be seen in the present village locations. Meanwhile, the ancient settlement pattern in a village has elements of a functional settlement pattern, namely a place to live, and a grave. A place of defense which is one of the elements of settlement, utilizing mountain rivers and oceans for this purpose.